Elevated Circulating Trimethylamine N-Oxide Levels Contribute to Endothelial Dysfunction in Aged Rats through Vascular Inflammation and Oxidative Stress - Li, Tiejun; Chen, Yanli; Gua, Chaojun; Li, Xiaodong (Frontiers in Physiology, 2017)
Vascular endothelial dysfunction, a characteristic of the aging process, is an important risk factor for cardiovascular disease in aging. Although vascular inflammation and oxidative stress are major contributors to endothelial dysfunction in aging, the underlying mechanisms during the aging process are not fully understood. Accumulating evidence reveals that gut microbiota-dependent metabolite trimethylamine-N-oxide (TMAO) is implicated in the pathogenesis of many cardiovascular diseases. We tested the hypothesis that aging increases circulating TMAO levels, which induce vascular inflammation and oxidative stress, resulting in age-associated endothelial dysfunction. Old (22-mo-old) and young (4-mo-old) Fischer-344 rats were treated without (control) or with 1.0 % 3,3-Dimethyl-1-butanol (DMB, an inhibitor of trimethylamine formation) in drinking water for 8 weeks. Compared with young control group, old control group had markedly higher plasma TMAO levels, which were reduced by DMB treatment. Endothelium-dependent relaxation of aorta in response to acetylcholine was impaired in old control group compared with young control group as indicated by decreased maximal relaxation (Emax) and reduced area under the curve (AUC). Emax and AUC were both normalized in old rats treated with DMB. No difference in endothelial-independent relaxation in response to sodium nitroprusside was observed among groups. Molecular studies revealed that old control group exhibits increased expression of proinflammatory cytokines and superoxide production, and decreased expression of endothelial nitric-oxide synthase (eNOS) in the aorta, all of which were restored by DMB treatment. These results suggest that aging increases circulating TMAO levels, which may impair eNOS-derived NO bioavailability by increasing vascular inflammation and oxidative stress, contributing to aging-associated endothelial dysfunction.